2022
DOI: 10.3390/met12081328
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mechanism of Abrasive-Based Finishing Processes Using Mathematical Modeling and Numerical Simulation

Abstract: Recent advances in technology and refinement of available computational resources paved the way for the extensive use of computers to model and simulate complex real-world problems difficult to solve analytically. The appeal of simulations lies in the ability to predict the significance of a change to the system under study. The simulated results can be of great benefit in predicting various behaviors, such as the wind pattern in a particular region, the ability of a material to withstand a dynamic load, or ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 248 publications
0
7
0
Order By: Relevance
“…software simulation-based techniques such as discrete element method, molecular dynamics simulation, finite element method, CFD and experimental techniques based on statistical software such as stochastic modeling & simulation by the data-dependent system, artificial neural network (ANN), response surface analysis and multivariable regression analysis (MVRA). The classification of modeling and simulation techniques for the evaluation and optimization of AFM process parameters (Hashmi et al , 2022b) is shown in Figure 35.…”
Section: Techniques For Improving the Surface Quality Of Additively M...mentioning
confidence: 99%
See 1 more Smart Citation
“…software simulation-based techniques such as discrete element method, molecular dynamics simulation, finite element method, CFD and experimental techniques based on statistical software such as stochastic modeling & simulation by the data-dependent system, artificial neural network (ANN), response surface analysis and multivariable regression analysis (MVRA). The classification of modeling and simulation techniques for the evaluation and optimization of AFM process parameters (Hashmi et al , 2022b) is shown in Figure 35.…”
Section: Techniques For Improving the Surface Quality Of Additively M...mentioning
confidence: 99%
“…As a result, it was found that a better surface finish could be achieved at 50% abrasive concentrations over a long finishing period. Similarly, Hashmi et al have also investigated the postprocessing of FDM-printed parts using the AFM process to improve their surface finish (Hashmi et al, 2021;Hashmi et al, 2022aHashmi et al, , 2022b. Leong et al (1998) have used the abrasive jet deburring process for surface finishing of SLA-based jewelry models.…”
Section: Thermal-based Surface Finishing Techniquesmentioning
confidence: 99%
“…The percentage of elements and the quantity of alloying elements used in magnesium determine its mechanical and corrosion behavior [21]. The outcomes of the simulations can be very helpful in forecasting a variety of behaviours material under static and dynamic conditions [22]. The mechanical and wear properties influencing parameters are explored for Al based metal matrix composites [23].…”
Section: Introductionmentioning
confidence: 99%
“…Nano-scale polishing of optical components can be realized by traditional polishing methods, including abrasive polishing [ 4 , 5 ], wet polishing [ 6 ], magnetorheological polishing [ 7 ], and ion beam machining [ 8 ]. H. Cheng et al put forward a magnetorheological fishing (MRF) [ 9 ] process for aspheric silicon carbide mirrors.…”
Section: Introductionmentioning
confidence: 99%